New Spectrophotometric Method for the Determination of Bosentan - An Anti-Hypertensive Agent in Pharmaceutical Dosage Forms - A. Narendra; D. Deepika; M. Mathrusri Annapurna (E-Journal of Chemistry)
A new, simple and sensitive spectrophotometric method in ultraviolet region has been developed for the determination of Bosentan in bulk and in pharmaceutical formulations. Bosentan exhibits absorption maxima at 273 nm with apparent molar absorptivity of 1.3293×104 L/mol.cm in methanol and octane 1-sulfonic acid solvent mixture. Beer's law was found to be obeyed in the concentration range of 0.1-100 μg/mL. The method was validated as per the ICH guidelines.